Methods for Three-Dimensional All-Optical Manipulation of Neural Circuits - Ronzitti, Emiliano; Emiliani, Valentina; Papagiakoumou, Eirini (Frontiers in Cellular Neuroscience, 2018)
Optical means for stimulating and monitoring neuronal activity have provided a lot of insight in neurophysiology lately towards our understanding on how brain works. Optogenetic actuators, calcium or voltage imaging probes and other molecular tools combined with advanced microscopies allowed ‘all-optical’ readout and manipulation of neural circuits. Completion of this remarkable work evolves towards the three-dimensional (3D) manipulation of neural ensembles at high spatiotemporal resolution. Recently, original optical methods have been proposed for both activating and monitoring neurons in the 3D space, mainly via optogenetic compounds. Here, we review these methods and anticipate possible combinations among them.